2021
DOI: 10.3390/educsci11090541
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Parental Support for Numeracy and Literacy in Early Childhood

Abstract: Past research has examined parental support for children’s math and reading skills in the early years through parents’ reports of their activities with their children in somewhat inconsistent ways. In this study, we use data from a large sample of parents (n = 259; 103 males) collected through Amazon’s Mechanical Turk to examine dimensions of parental enrichment in both support for literacy and numeracy skills at home. Additionally, we examine how socioeconomic resources as well as parental beliefs relate to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 80 publications
(127 reference statements)
1
10
1
Order By: Relevance
“…Third, parental attitudes and digital competence shape most adolescents’ primary caregivers, first educators, and online supervisors. Parental support, facilitation, and encouragement of adolescents’ Internet use and modeling of how to access the Internet safely are critical factors in developing adolescents’ digital resilience ( 45 ). Conversely, when parents restrict their children’s digital devices or Internet use or monitor their online activities without positive encouragement or support, they may inadvertently diminish their children’s ability to build digital resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Third, parental attitudes and digital competence shape most adolescents’ primary caregivers, first educators, and online supervisors. Parental support, facilitation, and encouragement of adolescents’ Internet use and modeling of how to access the Internet safely are critical factors in developing adolescents’ digital resilience ( 45 ). Conversely, when parents restrict their children’s digital devices or Internet use or monitor their online activities without positive encouragement or support, they may inadvertently diminish their children’s ability to build digital resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Cooperation between teachers and parents is fundamental for the development of children's literacy skills. Many parents expect their children to have good literacy and numeracy skills when starting primary school, so they also supply homebased learning for their children (Elliott et al, 2021;Salminen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, parents emphasized reading more highly. As reviewed in Elliott et al (2021) [10], some studies have found positive associations between parents' ratings of importance and children's engagement in reading and mathematics activities [33], whereas others have not found such associations between parents' ratings of importance and children's academic skills [44].…”
Section: Parents' Beliefs About Their Role In Children's Learningmentioning
confidence: 99%
“…For example, the frequency of reading different types of books during this time period is positively associated with the development of children's reading skills [3,5]. A similar relation holds for mathematics activities and skill development ( [6,7]; for review, see [8]) although the relation is less clear cut for mathematics than literacy and varies, to a degree, across demographic groups [9,10]. Research also shows that parents' beliefs about their role in their children's learning and how to foster academic skills is positively and significantly related to the frequency of children's engagement in relevant reading and mathematics activities (e.g., [11]).…”
Section: Introductionmentioning
confidence: 99%